Pengaruh Customer Experience Terhadap Revisit Intention di Wisata Kuliner Bunderan Perumnas Cibeber Kota Cilegon - Nadea Rafika Fikri; Meutia Meutia; Ahmad Bukhari (Leuit (Journal of Local Food Security), 2020)
The purpose of this study is to analyze the influence between customer experience variables including physical environment, social interaction, accessibility, and emotional experience on variable revisit intention in culinary tour "Bunderan Perumnas Cibeber" Cilegon City and the contribution of customer experience variables to variable revisit intention with determination coefficient. The location of the study is determined purposively. The data collected is primary data obtained from observations and instruments, and secondary data obtained from library studies. The results of the study are known partially customer experience variables positively affect the variable revisit intention. Simultaneously the customer experience variable positively affects the revisit intention variable. The contribution of the variable customer experience to the variable revisit intention by 57.2% and 42.8% is explained by other variables outside of this study.